Academic Writing and Publishing: A NASIG Preconference Workshop. Issue 1 (1st May 2017) - Collins, Maria; Cook, Eleanor I.
ABSTRACT: The goal of this preconference was to guide aspiring academic librarians in understanding how to navigate scholarly publication requirements and be successful academic writers. The presenters provided tips for beginners as well as for those already engaged in a research agenda. One of the presenters is a published book and journal author and the other is the editor-in-chief of a major peer-reviewed library journal.